In the Street - Nason, Ruth (London Franklin Watts, 2007)
Find out what different buildings in the high street are for, how councils try to make our streets cleaner and safer and what streets looked like in the past.
Include Color Illustration, Glossary and Index
Keywords: Streets -- Great Britain -- Geography